Využití BAC klonů při studiu pohlavního chromosomu W obaleče jablečného Cydia pomonella (Lepidoptera: Tortricidae) - Dalíková, Martina (Jihočeská univerzita, 2009)
In the present study, the W sex-chromosome of the codling moth was studied by means of fluorescence in situ hybridization (FISH) with probes prepared from bacterial artificial chromosome (BAC), which were isolated from the codling moth BAC library. The BAC library was screened for clones derived from both the W and Z sex chromosomes using three sets of molecular markers of codling moth sex chromosomes. A total of 54 BAC clones have been obtained. In this work, only 3 W-derived BAC clones and 1 Z-derived BAC clone were further characterized by BAC-FISH mapping on chromosome preparations of pachytene oocytes; the other BAC clones have been retained for next studies. Whereas the Z-BAC probe provided a discrete hybridization signal on the Z chromosome, and surprisingly on the W chromosome, the W-BAC probes showed multiple hybridization signals distributed on the whole W chromosome, suggesting that they are mainly composed of repetitive sequences, which occur in multiple clusters on the W chromosome. The specific pattern of W-BAC hybridization signals along with the discrete signal of the Z-BAC enabled us to discriminate left/right orientation of both the W and Z chromosomes and examine specificity of W-Z pairing during meiotic prophase I.
BAC clones as a tool for the study of codling moth Cydia pomonella (Lepidoptera: Tortricidae) W chromosome
Keywords: bakteriální umělé chromosomy; pohlavní chromosomy; obaleč jablečný; W chromosom; bacterial artificial chromosomes; sex chromosomes; codling moth; W chromosome